G79 Beyond the conference: Getting orally presented education projects published. (27th April 2016) - Jacob, H; Ho, J; Connaire, S; Bearpark, N; Fertleman, C
Abstract : Aims: Doctors in training are frequently successful in getting their projects accepted for oral presentation at conferences. Far fewer publish their research in peer-reviewed journals, despite this being the best way of disseminating findings widely. This study sought to establish the success of presenters at the Education section of the annual Royal College of Paediatrics and Child Health (RCPCH) conference, in publishing their work in peer-reviewed journals. Methods: We undertook a retrospective search for all abstracts presented orally at the Education section of the RCPCH conference between 2002 and 2015. Two people independently searched for every author of each abstract using the MEDLINE database. We recorded all peer-reviewed publications of the presented work and calculated the lag time from presentation to publication. Results: A total of 132 abstracts were presented orally at the Education section of the annual conference during the study period. Of these, 38 (29%) had gone on to be published in peer reviewed journals at the time of the search in September 2015. The mean lag time between presentation and publication was 18 months (range 0–49 months). Conclusion: The rate of conversion from oral presentation to publication is comparable to previously published studies of other conference abstracts. This provides some reassurance that high quality abstracts are being selected for presentation. Nevertheless, unpublished abstracts represent a missed opportunity for clinicians to contribute to the published literature in medical education. Additionally, trainees and their senior colleagues may not be making the most of the opportunity to improve their curriculum vitae with a peer-reviewed publication. In future, presenters will be encouraged more explicitly to consider submitting their work for publication. Practical advice will be offered around how to prepare a manuscript, write a cover letter and respond to reviewers' comments. Further work will evaluate how the awarding of prizes for the best oral presentations impacts on their subsequent success in publication.